Portrait of King Haakon V - unknown:::Creator::::::::::::
King Haakon VII. On Nov. 15, 1946 the King awarded Steinbeck the Liberty Cross in recognition of the positive impact the novel "The Moon Is Down" had on Norwegian resistance fighters in World War II. Haakon VII was an elected king and an important symbol to the Norwegian people in the resistance to the German invasion and occupation.Digital copy only. No hard copy.